Au Hierarchical Nanostructure-Based Surface Modification of Microelectrodes for Improved Neural Signal Recording - Woo, Hyeonsu; Kim, Suhyeon; Nam, Hyoryung; Choi, Wonsuk; Shin, Kumjae; Kim, Kanghyun; Yoon, Seungbin; Kim, Geon Hwee; Kim, Jinseok; Lim, Geunbae (AMER CHEMICAL SOC, 2021)
Microelectrodes are widely used for neural signal analysis because they can record high-resolution signals. In general, the smaller the size of the microelectrode for obtaining a high-resolution signal, the higher the impedance and noise value of the electrodes. Therefore, to improve the signal-to-noise ratio (SNR) of neural signals, it is important to develop microelectrodes with low impedance and noise. In this research, an Au hierarchical nanostructure (AHN) was deposited to improve the electrochemical surface area (ECSA) of a microelectrode. Au nanostructures on different scales were deposited on the electrode surface in a hierarchical structure using an electrochemical deposition method. The AHN-modified microelectrode exhibited an average of 80% improvement in impedance compared to a bare microelectrode. Through electrochemical impedance spectroscopy analysis and impedance equivalent circuit modeling, the increase in the ECSA due to the AHN was confirmed. After evaluating the cell cytotoxicity of the AHN-modified microelectrode through an in vitro test, neural signals from rats were obtained in in vivo experiments. The AHN-modified microelectrode exhibited an approximate 9.79 dB improvement in SNR compared to the bare microelectrode. This surface modification technology is a post-treatment strategy used for existing fabricated electrodes, so it can be applied to microelectrode arrays and nerve electrodes made from various structures and materials.
Keywords: ARRAY TECHNOLOGY; GLASSY-CARBON; ELECTRODES; IMPEDANCE; STIMULATION; DEPOSITION